STUDI KEPUASAN PASIEN TERHADAP KOMUNIKASI TERAPEUTIK PERAWAT DALAM MELAKSANAKAN ASUHAN KEPERAWATAN - Ridwan, ahmad; Eka, Agustin (Akademi Keperawatan Pamenang, 2013)
One of source patient dissatisfaction is caused by less communication going on betweeen nurse with the patient. The purpose of this research is to describe patient satisfaction of therapeutic communication in the nurse implements the nursing care in Seruni room Kab.Kediri hospital.Research design used in this study was descriptive with the entire population of patients treated in Kab.Kediri hospitals Ruang Seruni totaling 119 average Â per month, the total sample of 45 respondents to the purposive sampling technique. The data collected using questionnaires. While variable in this study is about patient satisfaction therapeutic nurse communication.The results showed that of the 45 respondents surveyed the largest 36 respondents (49,0%) said they were satisfied with therapeutic communication provided by nurses.From the research, it is advisable for nurses to provide nursing care in accordance with the expectations of the patient, and can show the attitude - the attitude of patience, honest, humble, empathetic to the patient so that the patient will feel satisfied with the services provided by nurses.Â Keywords: Satisfaction, Patient, Therapeutic Communication